Regulation of Expression of Reactive Oxygen Intermediates During Plasmodium Infection to Reduce Immunopathology Provides a Possible Antioxidant Adjuvant to Enhance Anti-Malarial Drug Therapy - M.J. Al-Obaidi Mazen; W. Taylor-Robinson Andrew (International Journal of Clinical Microbiology, 2017)
Malaria is a mosquito-transmitted infectious disease caused by intracellular protozoan parasites of the genus Plasmodium. In the absence of prompt and appropriate treatment contraction of primary infection by a human being often represents a medical emergency since it may progress rapidly to life-threatening complications. Exposure to parasites activates the immune system resulting in, among other effects, the release of reactive oxygen intermediates (ROI). This has the potential to induce oxidative damage, thereby causing cellular destruction, and hence to have a severe effect on vital organs of the body. Overexpression of ROI leads to immunosuppression and is a causal factor in the development of malaria-related disease symptoms. However, the body possesses various defence mechanisms, notably including the production of antioxidants, which are capable of reducing the cellular effects of ROI. Antioxidants are either sourced exogenously from the diet or synthesized through different intracellular mechanisms. Antioxidants that include glutathione peroxidase, catalase, EDTA and vitamin C suppress the initial production of ROI. Others such as uric acid, superoxide dismutase and vitamin E may also inhibit potentially damaging products of ROI metabolism. Current anti-malarial drugs often have damaging side-effects, as exemplified by memory impairment following treatment for cerebral malaria. Recent studies have explored the potential use of antioxidants alone or in combination with anti-malarials as a therapeutic means to negate Plasmodium-induced oxidative stress and its associated metabolic complications. It is indicated that when utilized in an adjuvant capacity antioxidants of natural and synthetic origin may improve anti-malarial therapy by causing less damage to the host during malaria infection.
Keywords: Malaria